Sex/gender differences in individual and joint trajectories of common mental health symptoms in early to middle adolescence - Aja Louise Murray; Anastasia Ushakova; Lydia Speyer; Ruth Brown; Bonnie Auyeung; Xinxin Zhu (Wiley, 2022)
Abstract Background Early to middle adolescence is a critical period of development for mental health issues. Illuminating sex/gender differences in mental health trajectories in this period is important for targeting screening and preventive interventions; however, evidence to date on the extent and nature of sex/gender differences in common mental health issue trajectories in this period has produced mixed findings. There is a particular gap in our knowledge of sex/gender differences in the joint trajectories of commonly co‐occurring mental health issues in adolescence, given the strong tendency for mental health issues to co‐occur. Method We applied sex/gender‐stratified latent class growth analysis to an age‐heterogeneous cohort (age 10-15) derived from the population‐representative UK Household Longitudinal Study. We explored sex/gender differences in attention deficit hyperactivity disorder (ADHD) symptoms, internalizing problems, and conduct problems individually and jointly. Results We found indications of sex/gender differences in a number of areas. There were fewer classes in the optimal model to describe the heterogeneity in internalizing problems and conduct problems trajectories in males and females respectively. Further, for ADHD, affected males were more likely to enter adolescence with already elevated symptoms whereas affected female trajectories were characterized by an escalation of symptoms during adolescence. Conclusions There are sex/gender differences in the levels and trajectories of specific mental health symptoms in early to middle adolescence; however, in both males and females there is a strong tendency for multiple issues to co‐occur.